npj Unconventional Computing - Payne, Daniel; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
npj Unconventional Computing considers all aspects of research applying unconventional approaches to improve computing efficiency and performance. The journal covers a broad range of topics including but not limited to: Brain-inspired algorithms Quantum computing and quantum-inspired algorithms Molecular, and DNA computing Membrane computing and P systems Neuromorphic computing and brain-inspired architectures Amorphous computing and swarm robotics Cellular automata and complex systems Artificial life and evolutionary computation Chaos computing and dynamical systems Reversible and adiabatic computing Thermodynamic computing Probabilistic computing (p-bit computing) Superconducting computing Application of physical phenomena to computing Design, fabrication, and testing of unconventional hardware, physical substrates, and emerging technologies for computing The journal offers more choice to Nature Portfolio authors who are seeking a fully open-access and more inclusive platform for publishing their work. The journal is led by computing experts who collaborate to cultivate high-quality research. As part of the npj Series, this journal focuses on fostering global partnerships with the research community and other Springer Nature journals.
Keywords: Quantum computers; Computer science; Mathematics; Computers; 9; Computational neuroscience; Quantum Computing; Theory of Computation; Mathematics and Computing; Computer Hardware; Mathematical Models of Cognitive Processes and Neural Networks; Computational Neuroscience